An Effect of Increasing Flight Instructor Competence on Flight Students at API Diploma III Banyuwangi - Roby Muharomansyah (Budapest International Research and Critics University, 2021)
Starting from the establishment of the Banyuwangi Indonesian Pilot Academy, it was started with the Banyuwangi Flight Center. At that time, students who were taught were only limited to printing professional pilots or non-diploma. In carrying out the training, it refers to the civil aviation safety regulations, section 141. Banyuwangi Aviation Workshop is managerially fostered by the Secretariat of the Transportation Human Resources Development Agency and technically fostered by the Human Resources Development Center of Civil Aviation. Over time, the Banyuwangi Pilot Workshop has been transformed into a Banyuwangi Pilot Education and Training Center. At that time, he was still referring to the Civil Aviation Safety Regulations. At the time this journal was written, the Government Regulation on Higher Education from other Ministries had not been issued since Law No. 12 of 2012 concerning Higher Education. Where the regulation and implementation of education refers to the Ministry of Education and Culture, Research and Technology. Where the transformation must adjust the standards or regulations that apply to universities. At the time this journal was written, the Government Regulation on Higher Education from other Ministries had not been issued since Law No. 12 of 2012 concerning Higher Education. In this study, the author aims to prove to the public that several important aspects must be developed by a Flight Instructor beyond the technical competence and non-technical aspects. Among them are aspects of attitude, knowledge, general skills, and special skills. Therefore, the importance of this research is to prove how important it is for Flight Instructors to develop self-improvement, both technical and non-technical. Moreover, the graduates to be printed are transportation officers with a level five KKNI. With university standards, lecturers are required to have a Master's Qualification or Education. Therefore, the competency aspect must be adjusted to the level of a Lecturer so that he is eligible to become a Flight Instructor for a Level five KKNI Diploma Student.